CC1 "Persistent genital arousal disorder – the experience of a London Teaching Hospital". (30th June 2016) - Nyatsanza, Farai; Goldmeier, David
Abstract : Background: Persistent genital arousal disorder (PGAD) is a condition seen mainly in women characterised by spontaneous and often unrelenting sensation of genital arousal in the absence of sexual desire or stimulation. These sensations typically do not fully remit with orgasm and are by definition intrusive and distressing. The condition overlaps in some cases with pudendal neuralgia but needs to be differentiated from hypersexuality. Patients may present preferentially to GUM clinics in the knowledge that sexual symptoms will not be trivialised. Different opinions exist as to triggers, causes and treatment. Taking this into consideration we analysed a cohort of patients with PGAD assessing whether they were any common themes in terms of precipitating and relieving factors. Aim: To describe our clinical experience and ascertain number of patients with diagnosis, common themes and treatment modalities. Methods: 57 patients were diagnosed with PGAD since departmental code was introduced in 2006 and 39 patients notes were located and reviewed. Results: Of these 69% were in a relationship and 64% had no history of past sexual abuse. Relieving factors were also varied among the cohort including masturbation and distraction. 95% were referred for mindfulness cognitive behavioural therapy and 51% were on medication such as amitriptyline, gabapentin, venlafaxine and nortriptyline. 72% were referred for pelvic floor physiotherapy. Discussion: PGAD is rarely seen estimates say 1–6% are affected by this hence it is important as sexual health clinicians to be aware of it to reduce delays in diagnosis. Overall management of PGAD requires a holistic approach with multidisciplinary team involvement.